A digital production metering method for electrical submersible pumps wells based on system energy balance - Yang, Jiani; Zhao, Ruidong; Ma, Gaoqiang (Frontiers in Earth Science, 2026)
Conventional production metering in Electrical Submersible Pumps (ESPs) wells relies on devices such as surface flowmeters, test separators, and multiplex valves. However, these methods are limited by poor real-time performance and high infrastructure costs. Digital/Virtual Flow Metering (DFM/VFM) has emerged as a promising alternative to conventional methods. However, existing DFM/VFM methods remain immature, often suffering from low accuracy and limited applicability. To address these challenges, this study proposes a digital production metering method based on system energy balance. The proposed model is established based on the energy balance between the motor output and the pump input and incorporates corrections for fluid property variations between surface and downhole conditions. Unlike standard pump performance curves, which are derived from water tests, this study conducted laboratory experiments on an ESP system to char-acterize the effects of fluid viscosity (10–50 cP) and density (0.8–1.1 g/cm3) on its perfor-mance. The experimental data were used to calibrate the motor and pump performance curves, significantly improving its accuracy and applicability. The model was validated against production data from five wells with different displacement rates. The results showed deviations ranging from 0.19 m3/d to under 20 m3/d, indicating good accuracy. This model provides a precise and cost-effective alternative to digital flowmeters. By eliminating the need for surface flowrate metering devices, the method not only reduces capital and operational expenses but also advances the intelligence of field management.